Subcutaneous emphysema after treatment using air-abrasive device: a case report - Marcelo Bighetti Toniollo; Andrea Sayuri Silveira Dias Terada; Marco Aurelio Kenichi Yamaji (Brazilian Dental Science)
Subcutaneous emphysema is an event often generated by iatrogenic reason, caused by improper dissection of air into soft tissues and/or anatomical structures, causing edema and visually noticeable volumetric change in the area of the incident. The main etiological factor for this is the use of equipment such as syringe air or high-speed handpieces in surgical procedures of greater magnitude; however, subcutaneous emphysema may also occur in simple procedures, such as occurred in the present case report, using the air-abrasive device usually proper for prophylaxis execution. The aim of this article is to report the case and to describe the care to avoid such an event, describing proper procedures for the correct resolution of the case, as well as alert the professional of the risks and necessary precautions.